Disparate effects of insulin on isolated rabbit afferent and efferent arterioles. - Juncos, L A (1993)
Despite evidence that insulin per se may be an important regulator of glomerular hemodynamics, little is known about its direct action on the glomerular afferent arterioles (Af-Art) and efferent arterioles (Ef-Art), the crucial vascular segments that control glomerular hemodynamics. In the present study, we examined the direct effect of physiological concentrations of insulin on isolated microperfused rabbit Af- and Ef-Arts. After cannulation, vessels were equilibrated in insulin-free medium for 30 min. To determine whether insulin causes vasodilation or constriction, increasing doses (5, 20, and 200 microU/ml) were added to the bath and lumen of arterioles that were either preconstricted to 50% of control diameter with norepinephrine or left nonpreconstricted. Insulin caused no vasoconstriction in either Af- or Ef-Arts, but it reversed norepinephrine-induced constriction in Ef-Arts but not Af-Arts (suggesting a vasodilator action selective to the Ef-Art): at 200 microU/ml, insulin increased Ef-Art luminal diameter by 75.8 +/- 7.0% from the preconstricted level (n = 6; P < 0.008). The vasorelaxant effect of insulin on Ef-Arts was not affected by blockade of either endothelium-derived relaxing factor/nitric oxide or prostaglandin synthesis. Despite the lack of effect of insulin on Af-Art when added after the equilibration period, when Af-Arts were equilibrated in the presence of either 20 or 200 microU/ml insulin, their basal diameter was significantly reduced (11.7 +/- 0.9 microns; P < 0.025, n = 6, and 12.0 +/- 0.9 microns; P < 0.025, n = 7, respectively) compared with nontreated Af-Arts (16.2 +/- 1.3 microns; n = 7). In conclusion, this study demonstrates that at physiological concentrations, insulin dilates NE-constricted Ef-Arts, while insulin pretreatment enhances Af-Art tone. The disparate actions of insulin on the Af- vs the Ef-Art may contribute to its beneficial effect on glomerular hypertension.